Glucocorticoid boluses followed by tocilizumab in giant cell arteritis patients: effects on peripheral blood monocytes and lymphocytes - Catellani, Cecilia; Bonacini, Martina; Rossi, Alessandro; Ferrigno, Ilaria; Buia, Veronica; Marvisi, Chiara; Cassone, Giulia; Catanoso, Mariagrazia; Di Tommaso, Gabriella; Boiardi, Luigi; Durmo, Rexhep; Versari, Annibale; et al. (Frontiers in Immunology, 2025)
IntroductionGiant Cell Arteritis (GCA) is the most common vasculitis in the elderly, characterized by granulomatous infiltration of immune cells in medium and large arteries. A therapeutic protocol that combines ultra-short glucocorticoids (GC) followed by tocilizumab (TCZ) monotherapy has been proven effective in GCA patients with extracranial large vessel involvement (LV-GCA). However, its effects on circulating immune cells are unknown. The aim of this study was to deepen the understanding of the immunological mechanisms behind this treatment regimen in patients with LV-GCA.Methods15 patients with active LV-GCA were included in this study. Blood samples were collected at baseline, after 3 days of GC treatment, at weeks 24 and 52 during TCZ monotherapy, and at week 78 after the suspension of TCZ. Peripheral blood mononuclear cells were isolated from blood samples. The percentages of lymphocyte and monocyte subsets and the expression of the monocyte markers CCR2, CX3CR1, and HLA-DR were analyzed by flow cytometry. Paired Student’s t-test and mixed-effects analysis were used for the comparison between and among groups, respectively.ResultsGC boluses increased the percentages of B lymphocytes and classical monocytes while decreased those of CD4+ T lymphocytes and intermediate and non-classical monocytes. Moreover, GC boluses increased CCR2 and decreased HLA-DR and CX3CR1 expression by monocytes. TCZ induced a reduction in CCR2 expression versus baseline in classical and intermediate monocytes. Patients with higher reduction in CCR2 expression in intermediate monocytes at 24 weeks and 52 weeks versus baseline showed signs of disease activity at 78 weeks.ConclusionGC boluses modified the relative percentages of lymphocyte and monocyte subsets and modified the expression levels of CCR2, CX3CR1, and HLA-DR in monocytes. These changes may contribute to the anti-inflammatory effects of GCs. TCZ monotherapy had more limited effects. Changes in CCR2 expression by intermediate monocytes might have a prognostic value in LVV.